Prospects for dilepton rates from lattice QCD. (March 2015) - Francis, Anthony
Abstract: We discuss the prospects of computing thermal dilepton rates from first principles lattice QCD. The focus lies in the determination of the meson vector-vector current spectral function to estimate the electrical conductivity, heavy quark diffusion and quarkonium dissociation. We review and compare recent results from continuum-extrapolated, quenched calculations, as well as dynamical two-flavor setups.